Taxonomic study of Calliandra (Leguminosae, Mimosoideae) in the State of Pará, Brazil - Reis, Agirlayne de Souza; Sousa, Julio dos Santos de; Bastos, Maria de Nazaré do Carmo; Silva, Wanderson Luis da Silva e (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
This study presents the taxonomic treatment for Calliandra Benth. in the Pará state. The methodology includes the analysis of botanical material originated from new collections and specimens herbaria Museum Goeldi (MG), Agronomic Institute of the North (IAN), National Institute of Research of the Amazon (INPA) and Rio de Janeiro Botanic Garden (RB). Identification key, descriptions, geographical distribution, comments and illustrations of species are provided. In Pará the genus is represented by ten taxa: Calliandra coriacea, C. glomerulata var. glomerulata, C. jariensis, C. laxa var. stipulacea, C. parviflora, C. parvifolia, C. purpurea, C. sessilis, C. surinamensis, and C. trinervia. Calliandra glomerulata var. glomerulata is a new record for the state.
Keywords: Amazon; Botany; Morphology; Taxonomy